Filsafat ilmu sebagai kritik atas budaya instan diera digitalisasi - Wafaa, Fardaa Naabih Saniyyatul (Maliki Interdisciplinary Journal, 2026)
The development of digital technology has accelerated public access to information through the internet and social media. This convenience brings many benefits, but it also fosters an instant culture, namely the tendency to seek quick answers without going through the processes of understanding, examining, and verifying information. This instant culture negatively affects the quality of knowledge because understanding often remains superficial and weakens critical thinking skills in evaluating information. In the digital era, the challenge becomes even greater as hoaxes and disinformation spread easily due to low verification habits and the influence of viral content, which attracts more attention than scientific information that requires deeper reasoning. In this context, the philosophy of science serves as a critique of instant culture by emphasizing that knowledge is not merely information, but must be supported by rationality, scientific methods, evidence, and logical consistency. The philosophy of science also highlights the importance of academic ethics, such as scientific integrity and responsibility in sharing information. Therefore, strengthening information literacy, developing the habit of checking sources, and cultivating critical thinking are essential efforts so that society can use technology wisely and produce knowledge that is more valid and accountable.